Adaptation of IUCN Classification Schemes for Environmental safety passports of species - Kryvomaz, Tetyana (My University, 2016)
This study aimed to improve the ways of risk assessment for environmental safety. The implementation of “Environmental safety passports of species” is of practical importance for effective risk assessment of individual species impact to the environment, humans and other living organisms. The classification schemes of International Union for Conservation of Nature for evaluating habitats, threats & stresses, use and trade, livelihoods of species were analyzed and adapted to the requirements of environmental safety. Some sections such as general information about species, their distribution, ecological classification, metabolism features, risks evaluation and beneficial use were itemized to be included into the structure of ESPS.
Keywords: environmental safety; risk assessment; evaluating schemes; certification